The Closure of a Shallow Tidal Inlet Promoted by Infragravity Waves. Issue 12 (28th June 2019) - Bertin, Xavier; Mendes, Diogo; Martins, Kévin; Fortunato, André B.; Lavaud, Laura
Abstract: Tidal inlets connect the ocean to inner water bodies and are present worldwide. Shallow inlets display fast morphological changes, due to complex interactions between tides, waves, and shallow depths. Their closure is commonly observed under storm waves, but the underlying processes remain only partly understood. Here, we present new field evidence that infragravity waves contribute to the closure of shallow inlets. The analysis of new field data collected at a shallow inlet under storm waves reveals that infragravity waves up to 0.4 m high can propagate inside the lagoon during flood but are blocked by opposing currents during ebb. At the passage of an infragravity wave crest, currents peak over 2.5 m/s and increase instantaneous sand fluxes by 2 orders of magnitude. Large accumulations of sand at the lagoon entrance damp tidal propagation until full inlet closure. This mechanism provides a new explanation for the closure of shallow inlets observed worldwide. Key Points: Under storm waves, infragravity waves up to 0.4 m high propagate through a shallow inlet at flood but are blocked at ebb At the passage of an infragravity wave crest, currents peak over 2.5 m/s and sand fluxes increase by 2 orders of magnitude Over a tidal cycle, large amounts of sand accumulate at the lagoon entrance, which damps tidal propagation and promotes inlet closure